ANALISIS EFEKTIVITAS BIMBINGAN KONSELING ISLAMI BERBASIS TAZKIYATUN NAFS TERHADAP PENURUNAN KECEMASAN - Vina Mafaza; Rizqi Nur Amalya; Muhammad Zufar Sabiq; M.Iqodzul Himam Abil Izz; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Anxiety is a psychological problem frequently experienced by adolescents and can impact academic, social, and mental health. This condition requires treatment that focuses not only on the psychological aspects but also on the spiritual dimension. One approach that can be used is tazkiyatun nafs (self-purification), a process of purifying the soul in Islam that aims to foster inner peace and closeness to Allah SWT. This study aims to analyze the effectiveness of the tazkiyatun nafs approach in reducing anxiety through a literature review. The method used was library research, collecting and analyzing various relevant scientific sources. The results indicate that tazkiyatun nafs is implemented through the stages of ihsan, takhalli, tahalli, and tajalli, which play a role in cleansing the soul of negative traits, instilling praiseworthy morals, and increasing spiritual awareness. Practices such as dhikr (remembrance of God), prayer, reading the Quran, self-reflection (muhasabah), and tawakkul (religious devotion) help reduce negative thoughts, improve emotional regulation, and foster inner peace. Thus, tazkiyatun nafs (self-care) has the potential to be an effective Islamic counseling approach to reducing anxiety and supporting more balanced mental and spiritual health.